Convergence is NOT King - The Triadic Phenomenon of Media "Convergence-Divergence-Coexistence" IS King - Lugmayr, Artur; Dal Zotto, C. (Springer Berlin Heidelberg, 2016)
This chapter presents the triadic phenomenon of “convergence-coexistence-divergence” as model for describing the dynamics of current developments taking place within the media industries. Indeed, convergence and divergence processes happen in parallel, thus coexisting, as well as at different levels influencing each other. The variety of contributions to this edited book testifies this evolution and the analysis of the 38 book chapters that we have been conducting to conclude the study well shows it. By applying a qualitative and quantitative methodology to analyze the content of the different chapters we shed light on the reasons why convergence is not the only king driving the evolution process within the media industry, but on the contrary it shares the driver’s seat together with divergence and coexistence factors. Several practical examples as well as links for further reading enrich the chapter.